THE COURT’S PROVISION OF REASONABLE TIME IN CRIMINAL PROCEEDINGS - Borodinova, Tatyana; Mikhaylovich , Vladimir; SkachkoMikhaylovich , Anna; Gaevoy, Alexander; Petrikina, Anna (Revista Inclusiones, 2020)
This article aims to define theoretical and practical importance of the “reasonable time” principle in criminal proceedings. We analyze the conceptions of legal developments on reasonable time in criminal proceedings as regards the efficiency of justice. The position of the European Court of Human Rights and the Russian comprehension of the regulations on reasonable time in pretrial proceedings serve as a basis for determining importance and correlation between circumstances considered in setting reasonable time. We analyze legislative rules on determining reasonable time in criminal proceedings and the possibilities of parties to participate in accelerating procedures.